FAKTOR-FAKTOR YANG BERPENGARUH PADA PEMILIHAN METODE AKUNTANSI PERSEDIAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PADA PERIODE 2013-2015 - Fitri Cahyanti, 10.05.52.0101; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2017)
The research aims to analyze the selection that influence a company's decision to use the methods of inventory valuation. The research examines six independent variables were it tested, firm size, managerial ownership, current ratio, financial leverage, inventory intensity, and variability of cost of goods sold. While the dependent variable is the inventory valuation method that is the FIFO method and the average method. The sample of this research are manufacturing companies listed on Indonesia Stock Exchange (IDX) from 2013-2015 were selected using purposive sampling method. The number of samples used counted 270 data from a population of 458 companies. The data used in this research is secondary data. The method of analysis used in this research is logistic regression analysis. The results showed that firm size, managerial ownership, and inventory intensity have a positive influence on the selection of inventory accounting methods. The current ratio, financial leverage and the variability of cost of goods sold have no influence on the selection of inventory accounting methods.Keywords: Inventory Accounting Method, FIFO Method, Average Method